2023
DOI: 10.1001/jamapsychiatry.2022.4234
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Polygenic Risk Score Loading, Psychosis Liability, and Clozapine Use Among Individuals With Schizophrenia

Abstract: ImportancePredictors consistently associated with psychosis liability and course of illness in schizophrenia (SCZ) spectrum disorders (SSD), including the need for clozapine treatment, are lacking. Longitudinally ascertained medication use may empower studies examining associations between polygenic risk scores (PRSs) and pharmacotherapy choices.ObjectiveTo examine associations between PRS-SCZ loading and groups with different liabilities to SSD (individuals with SSD taking clozapine, individuals with SSD taki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is important to highlight that in most of the reviewed studies, high PGSSCZ was associated with poor treatment response 32–34, 37, 38, 40, 41, 43, 4547 , more treatment resistance 31, 35, 36, 42, 44 , more antipsychotics-induced side effects 4850 or more psychiatric hospitalizations 39 . A notable exception was a positive association with lower symptom burden in SCZ patient treated with clozapine 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to highlight that in most of the reviewed studies, high PGSSCZ was associated with poor treatment response 32–34, 37, 38, 40, 41, 43, 4547 , more treatment resistance 31, 35, 36, 42, 44 , more antipsychotics-induced side effects 4850 or more psychiatric hospitalizations 39 . A notable exception was a positive association with lower symptom burden in SCZ patient treated with clozapine 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 provides a summary of the findings extracted from each of the articles included in this systematic review (Table 1). Several studies (20 studies) revealed that individuals with higher genetic loading for SCZ had a poorer treatment outcome to psychiatric medications [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] , while the remaining studies didn't find significant associations. For example, in patients with SCZ, a negative correlation (r = -0.05[95%CI: -0.09 --0.01]) was found between PGSSCZ and response to second generation antipsychotics (olanzapine, aripiprazole, risperidone, quetiapine, haloperidol, ziprasidone, perphenazine) following six weeks treatment 34 dosing (>600 mg/day) suggesting that individuals with a higher PGSSCZ may require increased doses of clozapine to achieve effective treatment response 33 .…”
Section: The Association Of Pharmacogenomic Scores With Treatment Out...mentioning
confidence: 99%
“…Currently, personalized medicine approaches aim to optimize clozapine treatment further. These include developing predictive markers for treatment resistance [29 ▪▪ ,79,80 ▪▪ ], clozapine response [4 ▪ ,81,82], and adverse effects – especially agranulocytosis and myocarditis [83 ▪ ,84 ▪ ] – as well as individualizing dosing and switching regimes [85 ▪ ,86 ▪ ]. Moreover, studies designed to conclusively determine, whether clozapine might have disease-modifying properties and slow illness progression, when used very early [4 ▪ ], are urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Initial research into the potential diagnostic value shows that patients on clozapine have higher schizophrenia-PRSs than patients on other antipsychotic drugs during follow-up. 48 If this finding is confirmed in additional cohorts, PRSs could help identify individuals who might benefit from clozapine and thus ensure that clozapine treatment is started at the appropriate time. Given evidence of the increased likelihood of remission following ECT and clozapine treatments in patients with high schizophrenia PRSs, 49,50 future studies of clozapine-resistant schizo phrenia might uncover associations between PRSs and specific symptom domain improvements following augmentation strategies.…”
Section: Geneticsmentioning
confidence: 99%